2013
DOI: 10.1074/jbc.m113.510727
|View full text |Cite
|
Sign up to set email alerts
|

The Allosteric Mechanism of Activation of Antithrombin as an Inhibitor of Factor IXa and Factor Xa

Abstract: Background:The heparin activation mechanism of antithrombin as a factor IXa and Xa inhibitor is not established. Results: Mutations adjacent to helix D result in full activation of antithrombin without heparin. Conclusion: Activation is largely dependent on Tyr-131 and Ala-134 and minimally on reactive center loop hinge expulsion. Significance: This changes the understanding of the activation mechanism of antithrombin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 35 publications
(25 reference statements)
2
19
0
Order By: Relevance
“…The allosteric mechanism of AT activation upon heparin binding was re-examined by Dementiev and coworkers in order to understand the differential contributions of the helix D extension promoted by heparin binding in the region 131 YRKAQK 136 and the, possibly coupled, expulsion of the hinge of the reactive centre loop [36].…”
Section: Response To Wounding: the Coagulation Cascadementioning
confidence: 99%
“…The allosteric mechanism of AT activation upon heparin binding was re-examined by Dementiev and coworkers in order to understand the differential contributions of the helix D extension promoted by heparin binding in the region 131 YRKAQK 136 and the, possibly coupled, expulsion of the hinge of the reactive centre loop [36].…”
Section: Response To Wounding: the Coagulation Cascadementioning
confidence: 99%
“…A particularly notable recent report showed that an antithrombin variant fully activated without the need for heparin nevertheless retained an intact RCL-sheet A interaction (21). In view of such findings, we were interested in clarifying the role of the RCLsheet A interaction in the mechanism of heparin allosteric activation.…”
mentioning
confidence: 99%
“…Therefore, these variants indicate that the partial hinge insertion does not hinder the ability for CLIPB9 to target and cleave the SRPN2 RCL. These data can be interpreted in the context of a recently proposed expansion of the allosteric ATIII activation model (64). This model envisions that lowered activity of hinge-inserted ATIII in the absence of H5 is largely due to repulsive exosite interactions with factors IXa and Xa.…”
Section: Discussionmentioning
confidence: 99%